Stereological analysis of syncytiotrophoblast in resorption villi of placentas of young and older pregnant women - Sergije Marković; Zlata Žigić; Suada Ramić; Jasminka Hadžihalilović (Medicinski Glasnik, 2010)
Aim To determine quantitative parameters of volume density and absolute volume of syncytiotrophoblast in resorption villi of control and experimental group, compare the results and search for correlation between structural parameters of resorption villi and pregnancy age. Metods The research was performed on 60 human placentas of term pregnancy: 30 placentas of pregnant women of age 20 - 34 (control group), and 30 placentas of pregnant women of age 35 and older (experimental group). Stereological analysis was performed on multipurpose testing system M42 with 40 times objective magnification. Results Average volume density of syncytiotrophoblast in resorption villi of experimental and control group was Vvss = (0,489 ± 0,032) mm0 and Vvsm = (0,389 ± 0,078) mm0 , respectively. Statistical analysis of results using Student t-test indicated a significantly higher volume density of syncytiotrophoblast of resorption villi in the experimental than in the control group (p<0,001). Absolute volume of syncytiotrophoblast in resorption villi of the experimental and control groups was Vss =(205,250±40,894) cm3 and Vsm = (178,386 ± 44,413) cm3, respectively. We have found a significantly higher absolute volume of syncytiotrophoblast in resorption villi in the experimental than in the control group (p<0,005). Conclusion Statistically significant higher values of volume density and absolute volume of syncytiotrophoblast in resorption villi of placentas in older pregnant women represent a compensatory mechanism as a response to decreased metabolic exchange between a mother and a fetus.